Quantification of naphazoline nitrate by UV-spectrophoto-metry - O. I. Panasenko; A. A. Safonov; A. S. Gotsulya (Zaporožskij Medicinskij Žurnal)
One of the main tasks of pharmaceutical chemistry – medical drugs study. Spectrophotometry is widely used in studying of the structure and composition (complexes, dyes, analytical reagents, etc.) of various compounds. It widely used for qualitative and quantitative determination of substances (determination of elements traces in metals, alloys, technical facilities). The dependence between substance structure and its electronic spectrum is being studied by many researchers till nowadays.